الإصطلاحات والتجديدات التى قام بها الخليفة عمر بن عبد العزيز - Azini Bt Abd Aziz; أزيني بنت عبد العزيز (Universiti Sains Islam Malaysia, 2022)
This project paper discusses the topic related to innovations that were implemented by Umar Abdul Aziz during the period of his governance. It contains important issues such as the history of Umar, these innovations in politic, economic and societies. The method used in this study is based on library research. It is found that Umar Abdul Aziz was a good leader in the Umayyah Empire, and where his primary aim was his people's prosperity and he also maintained a moderated life style.